Microstructure, mechanical properties and interaction mechanism of seawater sea-sand engineered cementitious composite (SS-ECC) with Glass Fiber Reinforced Polymer (GFRP) bar - Wei, Jiaying; Ke, Linyuwen; Wang, Peng; Li, Weiwen; Leung, Christopher K.Y. (Composite structures, 2024)
With increasing demand for sustainable and long-lasting materials, seawater sea-sand engineered cementitious composite (SS-ECC) has emerged as a promising alternative to conventional concrete in near-ocean construction projects. Glass fiber reinforced polymer (GFRP) bar with excellent corrosion resistance is an ideal choice for these applications. This study evaluated the bond performance of GFRP bars embedded in normal-strength ECC with polyvinyl alcohol (PVA) fibers and high-strength ECC with polyethylene (PE) fibers through pull-out tests. Additionally, tests were conducted on GFRP bars in pristine ECC made with freshwater and river sand for comparison. Further investigation explored the structural properties and uncovered load transfer mechanisms. Results indicated that saline content facilitated early cement hydration of normal-strength ECC, resulting in finer pore structure (10.5% lower porosity and 12.5% lower sorptivity), slightly enhanced compressive performance (1.2% higher compressive strength and 8.3% higher elastic modulus), denser microstructure at GFRP-ECC interface (13.7% lower porous transition zone thickness, 19.2% narrower transition zone and 19.7% higher Ca/Si ratio), and superior bond performance (28.3% higher bond strength and 22.6% higher fracture energy). Conversely, saline content imposed a limited impact on the mechanical properties of high-strength ECC, primarily attributed to the ultra-fine microstructure and early strength characteristics exhibited by the silica fume (SF)-based cementitious binder.